COVID-19 and pregnancy: impact, outcomes, and potential therapy - V. I. Shcherbakov; T. I. Ryabichenko; O. O. Obukhova; T. V. Kartseva; V. E. Menshchikova; D. V. Eliseeva; M. I. Voevoda (Сибирский научный медицинский журнал, 2024)
The impact of the new coronavirus COVID-19 infection on the course of pregnancy, maternal and child health is largely unclear and controversial. The presented literature review analyzes changes in the immune, cardiovascular, and endocrine systems in women in physiological pregnancy. The peculiarities of the course of infection caused by SARS-CoV-2 virus in pregnancy, depending on the virus variant, are presented, the issues of infection pathways into immune and non-immune cells, including placental cells, as well as the issues of transplacental transfer of the virus – the key moment of infection of the embryo or fetus, on which the outcome of pregnancy also largely depends, are considered. Promising approaches to COVID-19 therapy are presented: use of inhibitors of transmembrane serine protease 2 (TMPRSS2), furin, angiotensin-converting enzyme (ACE2) and RNA-dependent RNA polymerase, amnion epithelial cells and their exosomes. At the same time, the potential use of mesenchymal stem cells in patients with severe COVID-19 pneumonia is reviewed. Difficulties and questions regarding the use of the above therapeutic methods in pregnant women are highlighted. Aspects of the use of surfactant preparations in newborns at risk of new coronavirus infection are considered.